2009
DOI: 10.1176/appi.ps.60.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Mental Health and Addictions Care in Urban Community Health Clinics: Frontline Provider Accounts

Abstract: The unique barriers to care in the community health care setting, as well as the unique characteristics of patients served, are likely to require context-specific solutions. These solutions will determine the viability of existing chronic disease management models, such as collaborative care, when applied to this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Few differences were found in the review of jurisdiction-specific clinician focus groups, other than language barriers in the system that treats many Spanish-speaking patients; thus, clinician themes were not further divided by jurisdiction. In general, the barriers described by informants mirror those found by other researchers who study access to mental health care (Cristofalo et al, 2009; Davis et al, 2008; Meredith et al, 2009). Prominent is the issue of “competing demands” because limited time is often cited by providers when managing mental health problems in primary care and because mental health problems are seen as too complex to manage (Klinkman, 1997).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Few differences were found in the review of jurisdiction-specific clinician focus groups, other than language barriers in the system that treats many Spanish-speaking patients; thus, clinician themes were not further divided by jurisdiction. In general, the barriers described by informants mirror those found by other researchers who study access to mental health care (Cristofalo et al, 2009; Davis et al, 2008; Meredith et al, 2009). Prominent is the issue of “competing demands” because limited time is often cited by providers when managing mental health problems in primary care and because mental health problems are seen as too complex to manage (Klinkman, 1997).…”
Section: Resultssupporting
confidence: 69%
“…Although there are reports of provider perspectives of barriers to mental health care among primary care patients in general, we are interested in trauma-related issues in particular (Cristofalo et al, 2009). The need for trauma-specific interventions is highlighted by a study by Davis et al (2008), who found that, among urban African-American medical patients with PTSD, only 13.3% had previous trauma-focused treatment.…”
mentioning
confidence: 99%
“…Addiction agencies serve clients with complex problems while dealing simultaneously with significant resource and time constraints [16,17]. Addiction agencies serve clients with complex problems while dealing simultaneously with significant resource and time constraints [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers often utilize qualitative methods, such as semi-structured interviews, to investigate complexities within the health care system and interactions between system members (Cristofalo et al, 2008;Glasgow, Lichtenstein & Marcus, 2003;Hohmann & Shear, 2002;Hsieh & Shannon, 2005;Whitley, Gingerich, Lutz, & Mueser, 2009). Semi-structured interviews allow participants to draw connections from their own experiences and elaborate on concepts of interest more freely than would be possible using quantitative methods.…”
mentioning
confidence: 99%